PLURALISME HUKUM DALAM PERBUATAN HUKUM PENGANGKATAN ANAK DI BALI - I Gusti Agung Ayu Sukma Sanjiwani (University of Udayana, 2015)
Children have an important significance in the family. Adoption means taking the responsibility of other people's children from their biological parents in legal way therefore the children have the same status in the family. In Balinese Custom’s law, Peperasan ceremony is an absolute requirement for adoption process. Based on Government Regulation No. 54 Year 2007 about Adoption on Article 8 Adoption customary local habits; and Adoption by the legislation. Adoption not only solved the national law but also the religious affair. Starting from these ideas, pluralism of law in the adoption of legal acts in Bali interesting to examine.